Sheep Milk: Physicochemical Characteristics and Relevance for Functional Food Development. Issue 2 (12th January 2017) - Balthazar, C.F.; Pimentel, T.C.; Ferrão, L.L.; Almada, C.N.; Santillo, A.; Albenzio, M.; Mollakhalili, N.; Mortazavian, A.M.; Nascimento, J.S.; Silva, M.C.; Freitas, M.Q.; Sant'Ana, A.S.; et al.
Abstract: Sheep milk has a high nutritional value and high concentrations of proteins, fats, minerals, and vitamins, as compared to the milks of other domestic species. The physicochemical and nutritional characteristics of sheep milk can be advantageous for the manufacture of products containing prebiotic ingredients and/or probiotic bacteria, which are major categories in the functional food market. Following this technological trend, this review will address the characteristics and advantages of sheep milk as a potentially functional food, as well as the development of sheep milk dairy products containing prebiotics and/or probiotics.